Standoff Optical Glucose Sensing in Photosynthetic Organisms by a Quantum Dot Fluorescent Probe - Li, Jinming; Wu, Honghong; Santana, Israel; Fahlgren, Mackenzie; Giraldo, Juan Pablo (ACS applied materials & interfaces, 2018)
Glucose is a major product of photosynthesis and a key energy source for cellular respiration in organisms. Herein, we enable in vivo optical glucose sensing in wild-type plants using a quantum dot (QD) ratiometric approach. The optical probe is formed by a pair of QDs: thioglycolic acid-capped QDs which remain invariable to glucose (acting as an internal fluorescent reference control) and boronic acid (BA)-conjugated QDs (BA-QD) that quench their fluorescence in response to glucose. The fluorescence response of the QD probe is within the visible light window where photosynthetic tissues have a relatively low background. It is highly selective against other common sugars found in plants and can be used to quantify glucose levels above 500 μM in planta within the physiological range. We demonstrate that the QD fluorescent probe reports glucose from single chloroplast to algae cells (Chara zeylanica) and plant leaf tissues (Arabidopsis thaliana) in vivo via confocal microscopy and to a standoff Raspberry Pi camera setup. QD-based probes exhibit bright fluorescence, no photobleaching, tunable emission peak, and a size under plant cell wall porosity offering great potential for selective in vivo monitoring of glucose in photosynthetic organisms in situ.